THE ROLE OF MOSQUES AS CENTERS FOR EDUCATION AND SOCIAL ENGAGEMENT IN ISLAMIC COMMUNITIES - Suud Sarim Karimullah (Jurnal Bina Ummat: Membina dan Membentengi Ummat, 2023)
The review identifies innovations and best practices that mosques can adopt in fulfilling their role in a changing Islamic Society. This study uses a literature study with integrative and comprehensive literature analysis in collecting, reviewing, and analyzing various literature sources relevant to the topic of study. The study results revealed that the mosque is not only a place of worship but an integral center of empowerment in strengthening the Islamic community's educational, social, and spiritual dimensions. The educational function within mosques provides a strong foundation in religious understanding, ethics, and practical skills. In contrast, the role of mosques in social services creates social solidarity and a deep sense of social responsibility. Mosques also play an essential role in developing individuals' religious identities, strengthening ties with the larger Muslim community, and motivating them to create positive change in society actively.